Answer:
x =
![$ (40)/(41) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/afzmqvp0pnz9ylb5xcq3rzxasn63yvlz8n.png)
y =
![$ (58)/(41) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/n17u6vbvz5zqwo4qwjk7ykkmvo4z10py5b.png)
Explanation:
A system of two equation with two variables is given.
We solve it by eliminating one variable first.
The equations are:
and
![$ 3x + 5y = 10 \hspace{20mm} \hdots (2) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ts7cish79wb47u88phbma436pc0pgw6e7k.png)
We can eliminate either x or y.
We will eliminate y.
To do that multiply Equation (1) by 5 and Equation (2) by 2.
We get:
and
![$ 6x + 10y = 20 $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/el7ipnuq8xqpnxxnm25du0l1j9endmj6z0.png)
Adding these two equations, we get:
![$ 35x + 6x = 40 $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hf69px1d59pf11updn2s77zpnshvide8eg.png)
![$ \implies 41x = 40 $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/or1fpmc9og1wnj64x9nf9gtbgck2d6kp50.png)
⇒ x = 40/41
We substitute the value of 'x' in Equation (1) (Can be substituted in Equation (2) as well). We get:
2y = 7x - 4
⇒ 2y =
![$7((40)/(41)) - 4 $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/eb9z0vyys8yufgbmvs48vufqeugirxudf7.png)
![$ \implies y = (140 - 82)/(41) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p2dlyuiresa4knkslyd4ks7bwnwnoahzlr.png)
![$ \implies y = (58)/(41) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t157rffb15lkdf15i25ce1tp341uw9igfx.png)
Therefore, (x, y) = (40/41, 58/41).